Macroeconomic policy formulation: functional finance versus sound finance. (1st January 2013) - Hart, Neil
Current macroeconomic policy formulation emphasises trade-offs associated with promoting economic recovery through expansionary fiscal policy and the need to deliver 'fiscal sustainability' defined in terms of stabilising and reducing government debt ratios. This paper argues that these 'tensions' do not emerge from a considered interpretation of orthodox macroeconomic theory, but instead from the self-imposed 'sound finance' constraints that governments have placed on the formulation of macroeconomic policies. Lerner's system of functional finance, said to have provided the logical framework for Keynes's policy, has been largely neglected in the recent literature and policy deliberation. This paper considers the relevance of Lerner's system of functional finance to contemporary macroeconomic policy formulation.